Efficacy of 0.5% Timolol Maleate and 0.2% Brimonidine Tartrate in Control of Raised Intra Ocular Pressure after Neodymium Yttrium Aluminium Garnet Laser Capsulotomy (Medical Forum Monthly, 2023)
Objective: To compare the efficacy of 0.5% timolol maleate and 0.2% brimonidine tartrate with respect to the reduction in intra ocular pressure after Neodymium YAG laser capsulotomy.Study Design: Randomized Controlled Trial studyPlace and Duration of Study: This study was conducted at the Department of Ophthalmology, Ayub Teaching Hospital Abbottabad for 8 months from 1st November, 2021 to 30th June 2022.Materials and Methods: The sample size was 60 (30 patients in each group) selected from eye OPD using consecutive sampling. Data was collected on a specially designed proforma. Data analysis was done using SPSS 20.0.Results: The mean age of study participants was 60.82±6.96 years with 26(43.33%) males and 34(56.67%) females. The efficacy of the timolol maleate was 25(83.3%) while efficacy of brimonidine tartrate was 14(46.6%) for reduction in intraocular pressure with a significant difference between the groups (p= 0.003)Conclusion: Timolol maleate was found to be superior in controlling spikes of raised intraocular pressure as compared to brimonidine tartrate. However when efficacy was stratified by age and gender of study participants, no statistically significant association was noted.